Guideline gynekologických zhoubných nádorů 2010. Primární chirurgická lécba zhoubných nádorů endometria - Svoboda, B; Líbalová, P; Kubecová, M; Rob, L; Freitag, P; Pilka, R S; Chovanec, J; Tikovský, K; Vernerová, Z; Oncogynecologic Section of the Czech Gynecologic and Obstetric Society (Ceska gynekologie, 2011)
OBJECTIVE: To develop guideline for primary surgical treatment of endometrial carcinoma. DESIGN: Review, consensus of expert group. SETTING: Dept. of Gynaecology and Obstetrics, 3rd Medical Faculty of Charles University in Prague. METHOD: A retrospective review of published data, analysis of statistic data from Czech Republic, consensus among proposers and opponents. RESULTS: The guideline recognizes endometrial carcinoma patients based on their risk and recommends type of surgical treatment for certain group. It emphasizes the importance of centralized oncogynaecological treatment. Surgical staging remains the basic principle for treatment of endometrial carcinoma patients. The aim of pre-operative diagnostics is to estimate the extent of the disease--"interim staging", that can be different from definitive histopathological staging. Based on risk factors patients are divided into low or high risk group. Standard procedure for low risk patients is hysterectomy and bilateral salpingoophorectomy. It is advisable to use peroperative biopsy in these patients that can shift the patient to high risk group. High risk patients are recommended for hysterectomy, bilateral salpingoophorectomy, and systematic aortopelvic lymphadenectomy. The guideline contains recommendation for young patients wishing to preserve their fertility, for cases of inadequate surgery and for follow-up. CONCLUSION: Guideline for treatment of endometrial carcinoma is recommendation for clinicians and other subjects who participate on the process of the diagnostics/treatment of endometrial carcinoma patients. All points of the guideline were discussed and voted about by all participants of expert group.
Keywords: klinické protokoly; ženské pohlaví; Humans; lidé; Female; nádory endometria; Endometrial Neoplasms; Clinical Protocols